The significance of structural stigma towards transgender people in health care encounters across Europe: Health care access, gender identity disclosure, and discrimination in health care as a function of national legislation and public attitudes - Felicitas Falck; Richard Bränström (BMC Public Health, 2023)
Abstract Background According to the minority stress theory, stigma affects the health of marginalized populations. Previous stigma research has focused on the health effects of individual and interpersonal stigma, paying less attention to structural factors. Laws on legal gender recognition affect the lives of transgender individuals in unique ways. The fact that these laws and population attitudes vary greatly between European countries, offer a unique opportunity to study the role of structural stigma in the lives of transgender individuals. Little is known about how transgender specific structural stigma relates to individual health determinants. Consequently, the aim of this study was to explore the association between structural stigma and access to gender affirming care, gender identity disclosure in health care, and experiences of discrimination in health care across 28 European countries. Methods By using multilevel regression, we combined data on health seeking behavior, transgender identity disclosure to health care providers, and experiences of discrimination in health care from 6,771 transgender individuals participating in the 2012 European Union Lesbian, Gay, Bisexual and Transgender survey with a structural stigma measure, consisting of population attitudes towards transgender individuals as well as national legislation on gender recognition. Reasons to refrain from seeking care and discrimination in health care were assessed by categorizing countries as low or high in structural stigma and using Chi-square statistics. Results Country-level structural stigma was negatively associated experiences of seeking gender affirming care and positively associated with concealment of being transgender to health care providers. Identity concealment was associated with a lower likelihood of exposure to discrimination in the health care setting across countries regardless of their level of structural stigma. The most prevalent reasons to forgo gender affirming care were shared between low and high structural stigma country groups and centered around fear. Conclusion The results highlight the importance of changing stigmatizing legislation and population attitudes to promote access to gender affirming care as well as openness of being transgender towards providers. Measures to decrease discrimination in the health care setting are warranted in high as well as in low structural stigma countries.